Correlation between Gender and Study Period with Clean and Healthy Living Behavior in Nursing Students - Said Taufiq; Fitriani Agustina; Irwani Sofiati; Nonong Hanis; Nora Usrina; Desiana Desiana (Poltekkes Kemenkes Aceh, 2025)
Background: Clean and Healthy Living Behavior in nursing students plays a strategic role not only in maintaining individual health but also as a foundation for developing promotive and preventive competencies that will be applied in nursing practice. Variations in characteristics such as gender and study period have the potential to be factors in the implementation of PHBS in students. Purpose: To find out the implementation of Clean and Healthy Living Behavior and the relationship between gender and study period of students with Clean and Healthy Living Behavior in the Diploma III Nursing Study Program in North Aceh, Poltekkes Kemenkes Aceh. Methods: This type of quantitative research uses an analytical approach and a cross-sectional design. The study population was all students of the Diploma III Nursing Study Program in North Aceh, Poltekkes Kemenkes Aceh, with a sample of 132 students selected using a proportional stratified random sampling technique. The instrument used was a Clean and Healthy Living Behavior questionnaire whose validity had been tested (r count value > r table). Data analysis included univariate and bivariate analysis using the Chi-Square test with a significance level of α = 0.05. Results: There were 77.1% of students who had good Clean and Healthy Living Behavior implementation and 22.9% were in the poor category. The results of the bivariate analysis test showed a significant relationship between gender (p = 0.041) and study period (p = 0.032) with Clean and Healthy Living Behavior implementation in Diploma III Nursing Study Program students. Conclusion: The majority of Diploma III Nursing students demonstrate good practice of Clean and Healthy Living Behaviors. However, efforts are still needed to improve aspects such as regular health check-ups and physical activity. Furthermore, the length of study period has the potential to improve Clean and Healthy Living Behavior implementation, so a longer study period could provide a greater opportunity for optimal implementation.